2008
DOI: 10.1001/archopht.126.9.1252
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Golf-Related Ophthalmic Injuries

Abstract: To document ophthalmic morbidity of golfrelated injuries in children and to report specific injury patterns. Design: A noncomparative, interventional, retrospective case series of 11 pediatric patients treated at 2 institutions for ophthalmic trauma resulting from golfrelated injuries during 15 years. Results: Eleven eyes of 11 patients were injured. There were 6 boys and 5 girls, with a mean age of 10.2 years (age range, 7-14 years). Ten patients were injured by golf clubs and 1 patient by a golf ball. One in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Of the 22 patients described herein, 40.9% had open-globe injuries and 22.7% eventually underwent enucleation. The BETT provided a simple, comprehensive, and unambiguous method for describing GROIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12] Of the 22 patients described herein, 40.9% had open-globe injuries and 22.7% eventually underwent enucleation. The BETT provided a simple, comprehensive, and unambiguous method for describing GROIs.…”
Section: Discussionmentioning
confidence: 99%
“…If ocular injury occurs by direct impact while the golf ball is traveling at a high velocity, globe rupture is hard to avoid. [7][8][9][10][11] Even in penetrating injuries caused by broken glasses, the direct impact may result in extensive eyewall injuries, as occurred in Cases 6 and 7. These explanations could also account for the mechanism of orbital wall fracture in GROIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, of the 6 studies which describe visual acuity, 34 (47.9%) out of the 71 patients had significant reductions in visual acuity below 20/40 Snellen, including those with no light perception [ 8 – 13 ]. As most studies reported visual acuity using the 20-foot US Snellen notation, this same notation was used for this review [ 8 , 9 , 11 , 12 ]. For studies using the 6-meter UK based notation [ 10 , 13 ], visual acuity changes below 6/12 were recorded and used to demonstrate impairment in visual acuity.…”
Section: Resultsmentioning
confidence: 99%
“…This review regards any changes to visual acuity as a result of GROI as significant. Globe rupture was reported in 26 cases of which 22 (84.6%) were the result of impact from golf balls.Orbital fractures were reported in 5 studies [ 8 , 9 , 11 – 13 ] and were present in 30 (50%) out of the 60 patients reported.…”
Section: Resultsmentioning
confidence: 99%